DAMAGE AND LIFE ANALYSIS OF HIGH-PRESSURE TURBINE BLADES - Wang, Zhexin; Yang, Xiaoxu (Collection of scientific papers «ΛΌГOΣ», 2022)
The aeroengine is a highly complex and precise thermodynamic machine. As the heart of the aircraft, it is not only the driving force for aircraft flight but also an important driving force for the development of aviation. Every important change in the history of human aviation is related to the technological progress of aero engines. After more than a hundred years of development, aeroengine have developed into mature products with extremely high reliability.